BIOGRAFI H.M AZALY DJOHAN. SH - Nurbani Nurbani; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The name H. Azaly Djohan is indeed very popular for the people of Riau Province, as a figure in the government who is a role model for the community. In his service in Riau Province, he has occupied many government structures, he is known as a firm leader, trustworthy and disciplined in various ways, he is also active in various organizations in Riau Province, and now he is the Chair of Kwarda Riau Province. He participated in fighting for Riau to become a Province in 1957 which held a congress aimed at making Riau province formed and separated from central Sumatra. This study aims to determine the overall biography of H.M Azaly Djohan. SH what is his role in the world of government and community organizations in Riau Province. using a qualitative approach, a type of research whose findings are not obtained through statistical procedures or other forms of calculation. This type of research is field research, namely research carried out by direct involvement in the field to explore and examine data relating to the title. The respondents in this study were friends and colleagues H.M Azaly Djohan. SH. While the technique of collecting data in this study was conducted using two methods, namely: interview and documentation study. The results showed that H.M Azaly Djohan. SH has a role in the government of Riau Province.Key Words: H.M Azaly Djohan. SH